FEATURES OF IMPLEMENTING A FOOD SAFETY MANAGEMENT SYSTEM IN THE PRODUCTION OF YEAST-LAMINATED PASTRY - Tiurikova, I.S.; Tkachenko, A.S.; Ivanov, A.O.; Miroshnichenko, D.V. (SWorld-Ger Conference proceedings, 2025)
The study examines the implementation of the Hazard Analysis and Critical Control Points (HACCP) system in the production of yeast-laminated pastry. The technological process was analyzed, critical control points were identified, and practical assessment